Development of criteria for identifying potentially inappropriate prescribing in older adults with cancer receiving palliative care (PIP-CPC). Issue 8 (November 2021) - Cadogan, Cathal A.; Murphy, Melanie; McLean, Sarah; Bennett, Kathleen; Hughes, Carmel M.
Abstract: Objectives: To develop criteria for identifying potentially inappropriate prescribing of medications for symptomatic relief in older adults (≥65 years) with cancer who are receiving palliative care and have an estimated life expectancy of <1 year. Materials and methods: A two-round Delphi exercise was conducted using web-based questionnaires. A panel of 18 expert stakeholders with expertise in palliative care, oncology and/or geriatric medicine across Ireland and the United Kingdom rated their level of agreement with each statement using a 5-point Likert scale and had the option of adding free-text comments throughout the questionnaire. A priori decision rules were used to accept or reject criteria. Results: Twenty-eight criteria were presented in Round 1. Group consensus was achieved for 15 criteria which were included in the final set of criteria. Following a review of the panel's ratings and additional comments for the remaining 13 criteria, four criteria were removed from Round 2. Group consensus was achieved for all nine criteria included in Round 2. The final set comprised 24 criteria relating to: anorexia-cachexia ( n = 1); anxiety ( n = 2); constipation ( n = 5); delirium (n = 1); depression ( n = 3); diarrhoea (n = 1); dyspnoea/breathlessness ( n = 1); fatigue ( n = 2); insomnia (n = 2); nausea and vomiting (n = 2); pain (n = 3); duplicate drug classes (n = 1). Conclusion: A consensus-agreed set of prescribing criteria has been developed for identifying potentially inappropriate prescribing of medications for symptomatic relief in older adults with cancer who are receiving palliative care and have an estimated life expectancy of less than one year. Future studies should examine the application and validity of these criteria.